Operation of a DSTATCOM in voltage control mode. - Mishra, M.K (IEEE Transactions on power delivery)
The paper presents the operating principles of a distribution static compensator (DSTATCOM) that is used to maintain the voltage of a distribution bus. A three-phase, four-wire distribution system is assumed in this study. A three-phase bridge inverter circuit that is supplied by two neutral-clamped DC storage capacitors realizes the DSTATCOM. Three filter capacitors, one for each phase, are connected in parallel with the DSTATCOM to eliminate high-frequency switching components. The voltage across the filter capacitor is controlled by a dead-beat controller to maintain the AC bus voltage. The magnitude of the bus voltage is chosen as nominal value, i.e., 1.0 p.u., while its phase angle is obtained through a feedback loop that maintains the voltage across the DC storage capacitors. Through detailed simulation and experimental results, it has been shown that the DSTATCOM can maintain the voltage against any unbalance and distortion in either the load or supply side.